Lived experiences matter: The role of mental health professionals’ psychological crises and vulnerability in shaping their health beliefs and concepts - Ponew, Angel; Brieger, Anna; Lust, Christian; Speerforck, Sven; von Peter, Sebastian; Stuetzle, Stefan (Frontiers in Psychiatry, 2023)
Background: Mental health professionals are often affected by mental health problems and disorders. Yet, the effects of these lived experiences on their causal beliefs and health concepts have not been investigated. The current study investigates how professionals' lived depressive experiences and their perceived vulnerability to mental illness affect their causal beliefs about mental disorders, their general concept of mental health and their specific concepts of depression and burnout. Methods: An online survey was conducted with 218 psychiatric mental health professionals from 18 psychiatric clinic departments in the German federal states of Berlin and Brandenburg, investigating their experiences with depression, self-assessed vulnerability, their causal beliefs of mental illness, their general health concept and specific illness concepts of depression and burnout. A path model was calculated to examine the relationships between these variables. Participants with and without lived experience of depression were grouped. Results: Lived experience of depression was indicated by 126 participants. For participants with no experience of depression, perceived vulnerability negatively predicted beliefs in biological causation, which positively predicted higher differentiation between depression and burnout. For participants with previous depression experiences, perceived vulnerability positively predicted beliefs in psychological and social causation. Continuum belief was predicted only in this group by the three variables of causal beliefs. Psychological and social causation was positively associated, while biological causes were negatively associated with continuum beliefs. Conclusion: Mental health professionals are not external to the clinical situation. Their lived experiences do matter, shaping their beliefs and concepts and, thus, possibly also their actions towards patients.